Traditional Chinese Medicine to the rescue of allopathic medicine in the co-adjuvant treatment of hepatocellular carcinoma - Sparkman, Jordan; Hernaez, Ruben; El-Serag, Hashem B. (Translational Gastroenterology and Hepatology, 2018)
Hepatocellular carcinoma (HCC) is the fourth leading cause of cancer-related death in the world, and is the fastest rising cause of cancer-related death in the United States (1). Surgical resection of HCC is a potentially curative treatment option that can be applied to patients with no cirrhosis or compensated cirrhosis and no significant portal hypertension. However, when patients are treated even at early stage (e.g., small or few tumors) with resection, the 5-year recurrence free survival (RFS) is as low as 30% (2) due to new tumors arising in the remaining diseased liver.